Relaï¿½ï¿½o entre alto comportamento sedentï¿½rio no lazer e baixa funcionalidade de idosos - Bertolini, Giovana Navarro [UNESP]; Dos Santos, Vanessa Ribeiro [UNESP]; Alves, Marcelo Josï¿½; Cervellini, Paulo Cesar Marini; Christofaro, Diego Giulliano Destro [UNESP]; De Santana, Luï¿½s Felipe Dutra [UNESP]; Gobbo, Luï¿½s Alberto [UNESP] (FapUNIFESP (SciELO), 2016)
Sedentary behavior refers to activities with low energy expenditure, usually performed in sitting or lying positions, and includes behavior belonging to the current lifestyle, such as watching television. In the course of aging, this activity is performed for longer periods by individuals on a daily basis. This is worrying, since aging associated with sedentary behavior accentuates functionality decline. The aim of this study was to analyze the relationship between high leisure-time sedentary behavior and low functionality in older adults. The sample consisted of 375 older adults aged 60-97 years (70 ï¿½ 7 years), and of these, 114 (30%) were men and 261 (70%) women. Functionality was assessed by two functional tests and information related to sedentary behavior was obtained using the self-reported physical activity questionnaire proposed by Baecke et al. The chi-square test was used to verify the association between sedentary behavior and functionality, and binary logistic regression analysis was used to build the multiple model. Older individuals with high leisure-time sedentary behavior were more likely to have low functionality [OR 2.57; 95% CI 1.40 to 4.71] and [OR 2.35; 95% CI 1.29 to 4.29] regardless of gender, age, smoking, osteoporosis, arthritis/osteoarthritis, low back pain and physical activity. Extended permanence in sedentary behavior was associated with low functionality in older subjects. Preventive measures to stimulate the practice of physical activities and encourage the reduction of time spent in sedentary activities such as watching television should be adopted by health professionals in an attempt to maintain functionality among older adults.
Relation between high leisure-time sedentary behavior and low functionality in older adults
Keywords: Aging; Functioning; Sedentary lifestyle